Moderating effect of APOE ε4 on the association of sleep disturbance and amyloid-β pathology among cognitively normal older adults - Feng, Shufei; Que, Jianyu; Wang, Qianwen; Yuan, Kai; Shi, Le (Frontiers in Aging Neuroscience, 2025)
BackgroundSleep–wake rhythms are critical for the development of Alzheimer’s disease (AD). However, the relationship of sleep disturbance, APOE ε4, and amyloid-β (Aβ) accumulation remains unclear. Thus, this study investigated the potential role of APOE ε4 allele in the association between sleep disturbance and brain Aβ burden among cognitively normal (CN) older adults.MethodsIn this cross-sectional study, data were obtained from the Alzheimer’s Disease Neuroimaging Initiative (ADNl) Database. The sample consisted of CN individuals aged between 55 and 90 years with Aβ positron emission tomography scan, APOE genotype, and sleep assessment using the Neuropsychiatric Inventory.ResultsThe study included 1,000 CN participants, including 134 individuals with sleep disturbances and 306 APOE ε4 carriers (APOE ε4+). After adjusting for sex, age, years of education, and marital status, sleep disturbance was not associated with a higher Aβ burden among participants. However, a significant interaction between sleep disturbance and APOE ε4 on regional standardized uptake value ratios was observed, such as in the left hippocampus. Subgroup analysis revealed that sleep disturbance could affect the AD-sensitive brain regions in the APOE ε4 + group. Furthermore, the subjective severity of sleep disturbance was linearly associated with a more significant Aβ brain burden in the APOE ε4 + group.ConclusionThis study demonstrated that CN individuals with both APOE ε4 + status and sleep disturbance exhibited greater Aβ burden. Understanding the relationship between sleep and Aβ in CN older adults may inform sleep interventions that could reduce early Aβ accumulation and delay the onset of cognitive dysfunction associated with early AD.